2018
DOI: 10.1037/spq0000221
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical exploratory factor analyses of the Woodcock-Johnson IV Full Test Battery: Implications for CHC application in school psychology.

Abstract: The Woodcock-Johnson (fourth edition; WJ IV; Schrank, McGrew, & Mather, 2014a) was recently redeveloped and retains its linkage to Cattell-Horn-Carroll theory (CHC). Independent reviews (e.g., Canivez, 2017) and investigations (Dombrowski, McGill, & Canivez, 2017) of the structure of the WJ IV full test battery and WJ IV Cognitive have suggested the need for additional factor analytic exploration. Accordingly, the present study used principal axis factoring (PAF) followed by the Schmid and Leiman (SL; Schmid &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 49 publications
7
18
0
Order By: Relevance
“…Similarly, the high H values (>.80) also suggests a dominant general factor that portends to be stable across studies. Thus, consistent with other frequentist EFA and CFA studies (e.g., Bodin, Pardini, Burns, & Stevens, 2009;Canivez, 2014;Canivez & McGill, 2016;Canivez, Watkins, & Dombrowski, 2016, 2017DiStefano & Dombrowski, 2006;Dombrowski, 2013Dombrowski, , 2014aDombrowski, , 2017bDombrowski, Watkins, & Brogan, 2009;Dombrowski, Canivez, Watkins, & Beaujean, 2015;Dombrowski, McGill, & Canivez, 2017a, 2017bWatkins & Beaujean, 2014) and consistent with Frazier and Youngstrom (2007), the DAS-II appears to be an instrument dominated by a general factor. Note.…”
Section: Pattern Of Subtest Loadingssupporting
confidence: 88%
“…Similarly, the high H values (>.80) also suggests a dominant general factor that portends to be stable across studies. Thus, consistent with other frequentist EFA and CFA studies (e.g., Bodin, Pardini, Burns, & Stevens, 2009;Canivez, 2014;Canivez & McGill, 2016;Canivez, Watkins, & Dombrowski, 2016, 2017DiStefano & Dombrowski, 2006;Dombrowski, 2013Dombrowski, , 2014aDombrowski, , 2017bDombrowski, Watkins, & Brogan, 2009;Dombrowski, Canivez, Watkins, & Beaujean, 2015;Dombrowski, McGill, & Canivez, 2017a, 2017bWatkins & Beaujean, 2014) and consistent with Frazier and Youngstrom (2007), the DAS-II appears to be an instrument dominated by a general factor. Note.…”
Section: Pattern Of Subtest Loadingssupporting
confidence: 88%
“…In school-aged normative and standardization samples (Dombrowski, 2013;Dombrowski & Watkins, 2013;McGill & Busse, 2015) as well as in students referred for special education services (Strickland et al, 2015a), g has been found to dominate the facture structure of scores from the WJ III COG, with the test producing, in many reports, "limited predictive effects" beyond g (McGill & Busse, 2015, p. 353). The same finding appears to hold true in the revised WJ-IV (Dombrowski et al, 2017(Dombrowski et al, , 2018. In this sense our findings hold implications for cognitive testing and cognitive theory outside of the specific context of the Amazon region: our results add further evidence to the contention that interpretation of the WJ III COG should potentially be restricted to the g-factor.…”
Section: Assessment Implicationssupporting
confidence: 80%
“…While some of these studies were of standardization samples, some EFA and CFA studies were of clinical samples (Bodin et al, 2009; Canivez, 2014a; Canivez, Watkins, Good, et al, 2017; Watkins, 2010; Watkins et al, 2006; Watkins et al, 2013). Furthermore, similar results have been reported with the Differential Ability Scales (DAS; Cucina & Howardson, 2017); DAS-II (Canivez & McGill, 2016; Dombrowski, Golay, McGill, & Canivez, 2018; Dombrowski, McGill, Canivez, & Peterson, 2019), Kaufman Adolescent and Adult Intelligence Test (Cucina & Howardson, 2017), Kaufman Assessment Battery for Children (KABC; Cucina & Howardson, 2017), KABC-2 (McGill & Dombrowski, 2018b), Stanford–Binet–Fifth Edition (SB-5; Canivez, 2008; DiStefano & Dombrowski, 2006), Wechsler Abbreviated Scale of Intelligence and Wide Range Intelligence Test (Canivez, Konold, Collins, & Wilson, 2009), Reynolds Intellectual Assessment Scales (Dombrowski, Watkins, & Brogan, 2009; Nelson & Canivez, 2012; Nelson, Canivez, Lindstrom, & Hatt, 2007), Cognitive Assessment System (Canivez, 2011), Woodcock-Johnson III (Cucina & Howardson, 2017; Dombrowski, 2013, 2014a, 2014b; Dombrowski & Watkins, 2013; Strickland, Watkins, & Caterino, 2015), and the Woodcock-Johnson IV Cognitive and full battery (Dombrowski, McGill, & Canivez, 2017a, 2017b), so results of domination of general intelligence and limited unique measurement of group factors are not unique to Wechsler scales. These results and the advantages of bifactor modeling for understanding test structure (Canivez, 2016; Cucina & Byle, 2017; Gignac, 2008; Reise, 2012) indicate that comparisons of bifactor models to the higher-order models are needed.…”
Section: Discussionmentioning
confidence: 99%